Generation and functional characterization of epithelial cells with stable expression of SLC26A9 Cl− channels - Salomon, Johanna J.; Spahn, Stephan; Wang, Xiaohui; Füllekrug, Joachim; Bertrand, Carol A.; Mall, Marcus A. (American journal of physiology. Lung cellular and molecular physiology, 2016)
Recent studies identified the SLC26A9 Cl− channel as a modifier and potential therapeutic target in cystic fibrosis (CF). However, understanding of the regulation of SLC26A9 in epithelia remains limited and cellular models with stable expression for biochemical and functional studies are missing. We, therefore, generated Fisher rat thyroid (FRT) epithelial cells with stable expression of HA-tagged SLC26A9 via retroviral transfection and characterized SLC26A9 expression and function using Western blotting, immunolocalization, whole cell patch-clamp, and transepithelial bioelectric studies in Ussing chambers. We demonstrate stable expression of SLC26A9 in transfected FRT (SLC26A9-FRT) cells on the mRNA and protein level.
Im Titel ist das Zeichen "−" hochgestellt
First published January 22, 2015
Gesehen am 08.05.2020